2009
DOI: 10.15560/5.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Angiosperms, climbing plants in tropical forests of southern Eastern Ghats, Tamil Nadu, India

Abstract: We provide a check list of angiosperm climbing plant species, along with their climbing modes, enumerated from a total of one hundred and fifty grids in tropical forests of southern Eastern Ghats, peninsular India. The Eastern Ghats constitute an important biodiversity area in India and have been studied earlier mainly for the floristics, and that too confined to a few prioritized sites. Lianas, the woody vines contribute substantially to the diversity and structure of most tropical forests. Yet, little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…After critical study and through literature survey, the distribution of this species was extended to coastal districts of Odisha. Its occurrence in Nellore district of Andhra Pradesh 18 and South Eastern Ghats of Tamil Nadu 26 and coastal part (present report) of Odisha confirms the south, western-ward and eastern coastal part extension of its distribution in the country. The field observation and review concluded that it is the new distribution of G. chinense in Odisha.…”
Section: Resultssupporting
confidence: 75%
“…After critical study and through literature survey, the distribution of this species was extended to coastal districts of Odisha. Its occurrence in Nellore district of Andhra Pradesh 18 and South Eastern Ghats of Tamil Nadu 26 and coastal part (present report) of Odisha confirms the south, western-ward and eastern coastal part extension of its distribution in the country. The field observation and review concluded that it is the new distribution of G. chinense in Odisha.…”
Section: Resultssupporting
confidence: 75%
“…Based on climbing guild descriptions in other studies (Muthuperumal & Parthasarathy 2009, Muthuramkumar & Parthasarathy 2000) we identified five commonly occurring climbing mechanisms for lianas in this study: hook climbers, root climbers, scramblers, tendril climbers and twiners. The frequency of each of these in both edge and interior zones were inventoried and relative abundance compared.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 32 species are used for human consumption, 27 species have medicinal uses, and 11 species are of multiple u ses. Muthumperumal and Parthasarathy ( 2009 ) r eported a list of angiosperm climbers (175 climbing plant species that belong to 100 genera and 40 families), along with their climbing modes in tropical forests of south Eastern Ghats, Tamil Nadu, India. Later, they (Muthumperumal and Parthasarathy 2013) provided a detailed account on the diversity, distribution, and resource values of woody climbers in the similar area.…”
Section: Climbing Phytodiversity In Indiamentioning
confidence: 99%